Application of Show and Tell Learning Strategy to Train Speaking Skills for XI Language Students Class of SMAN 9 Malang - Kezia Irma Dwi Anggun; Lilis Afifah (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2022)
This research was conducted to describe (1) the application of the show and tell strategy with the theme of Essen und Trinken in class XI of SMA Negeri 9 Malang, to know (2) student responses in the application of the show and tell strategy in learning German. This research used the descriptive qualitative method. The data were collected through observation and questionnaire. Sources of data in this study were 23 students of class XI Language SMA Negeri 9 Malang.This research indicates that the show and tell strategy can train students to speak German enthusiastically and confidently without fear. Students also showed a good response during learning by using the show and tell. Based on the description above, the show and tell can help students practice speaking a foreign language.